2006
DOI: 10.1152/ajprenal.00374.2005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of urinary excretion of phosphate, calcium, and uric acid in mutant NHERF-1 null mice

Abstract: . Longitudinal study of urinary excretion of phosphate, calcium, and uric acid in mutant NHERF-1 null mice. Am J Physiol Renal Physiol 290: F838 -F843, 2006. First published October 25, 2005 doi:10.1152/ajprenal.00374.2005.-NHERF-1 binds numerous renal protein targets, including the proximal tubule transporters Na ϩ /H ϩ exchanger 3 (NHE3) and Na ϩ -phosphate cotransporter 2a (Npt2a). Young NHERF-1 Ϫ/Ϫ male mice display defective targeting of Npt2a to apical membranes in the renal proximal tubule and manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…Our previous studies indicated that NHERF-1 Ϫ/Ϫ mice have a significant increase in the urinary excretion of uric acid compared with wild-type control animals (6). To study the role of NHERF-1 on uric acid uptake in renal proximal tubule cells, we prepared primary cultures of proximal tubule cells using wildtype and NHERF-1 null mouse kidneys.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies indicated that NHERF-1 Ϫ/Ϫ mice have a significant increase in the urinary excretion of uric acid compared with wild-type control animals (6). To study the role of NHERF-1 on uric acid uptake in renal proximal tubule cells, we prepared primary cultures of proximal tubule cells using wildtype and NHERF-1 null mouse kidneys.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that NHERF-1 Ϫ/Ϫ mice excrete increased amounts of uric acid compared with wild-type controls (6). These studies were initiated to define further the relation between this adaptor protein and uric acid excretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NHERF-1 knockout mice have shown increased urinary calcium, phosphate, and uric acid excretion, resulting in tubulo-interstitial crystal deposits in the kidney [63]. Similar to NHEFR-1 mice, Npt2a knockout mice demonstrated hypercalciuria and renal crystal deposits in the kidney [54].…”
Section: Na þ -Phosphate Transportermentioning
confidence: 96%